Foreign-domestic substitution, import penetration and CGE modelling. Issue 35 (27th July 2021) - Clements, Kenneth W.; Mariano, Marc Jim M.; Verikios, George
ABSTRACT: Foreign-domestic substitution elasticities (the so-called 'Armington elasticities') determine the degree of competitiveness in demand between similar products produced in different countries and are key parameters in a variety of numerical models of international trade. Armington elasticities are part of the explanation of the large increases in market shares of foreign products relative to locally produced ones in Australia, for example. The existing literature provides only limited evidence on these elasticities for Australia with the most disaggregated produced some time ago in 1977 by Alaouze and colleagues. This paper provides up-to-date parametric estimates of Armington elasticities for Australia with a reasonable degree of sectoral disaggregation. We use 22-years of data for 20 types of merchandise commodities, using OLS, panel and restricted-panel approaches. Our estimates range from 0.30 to 2.26, with higher elasticities for Transport and Equipment products and lower ones for Energy and Minerals. We illustrate the use of our elasticities with a trade-policy simulation using a computable generable equilibrium model of the Australian economy. We analyse the sensitivity of the results to the Armington elasticities by also using the previous estimates of Alaouze and colleagues. We find an overestimation of economic effects when using the old Armington values.